Investigation of electrical properties and PTCR effect in double-donor doping BaTiO3 lead-free ceramics - Chen Xiaoming; Li Yini; Zeng Sikang; Cheng Xuxin; Zhang Wei; Wang Yuxin (High Temperature Materials and Processes)
Utilizing the conventional approach, the positive temperature coefficient of resistivity (PTCR) performance of lead-free ceramics based on (1 − x%)(Ba1−y Yy)(Ti1.011−z Nb0.001Mnz)O3 − x%(Bi0.5Na0.5)TiO3 (BBNTx) was examined. The BBNTx ceramics were prepared using the double donor dopant under firing at 1,350°C for 120 min in the air. The findings exhibited that when the Y3+ concentration elevates, the room-temperature resistivity of 99%(Ba1−y Yy)(Ti1.011−z Nb0.001Mnz)O3 – 1%(Bi0.5Na0.5)TiO3 (BBNT1) samples initially falls and subsequently elevates. Moreover, the critical content of the samples is 0.15 mol%. Furthermore, the samples’ resistance jumping ratio can be effectively improved by adding Mn2+. The manganese dioxide level of 0.05 mol% yields the greatest resistance-jumping ratio. Besides, the impact of (Bi0.5Na0.5)TiO3 (BNT) concentration on ceramics’ Curie temperature was examined in the work. Therefore, good free-lead PTCR thermistors were successfully prepared by doping 3% BNT, with a resistance jump of 4.1 magnitude.